An "evidence centre" in a general hospital: finding and evaluating the best available evidence for clinicians. Issue 4 (1st August 1999) - Anderson, Jeremy; Burrows, Elizabeth; Fennessy, Paul; Shaw, Sue
Abstract : Muir Gray describes the problem well: "Busy clinicians are now caught in an information paradox—overwhelmed with information but unable to find the knowledge they need when they need it…The truth is that information cannot be dealt with by individuals alone. The organisation in which individual clinicians work has to manage knowledge as well as it manages its other resources" (1).